Trends in marijuana use among pregnant women with and without nausea and vomiting in pregnancy, 2009–2016. (1st March 2019) - Young-Wolff, Kelly C.; Sarovar, Varada; Tucker, Lue-Yen; Avalos, Lyndsay A.; Alexeeff, Stacey; Conway, Amy; Armstrong, Mary Anne; Weisner, Constance; Campbell, Cynthia I.; Goler, Nancy
Highlights: Women may treat nausea and vomiting in pregnancy (NVP) with marijuana. We examined trends in prenatal marijuana use from 2009 to 2016 by NVP status. Prenatal marijuana use was elevated each year from 2009 to 2016 in women with NVP. The overall prevalence of prenatal marijuana use increased over time. Women with NVP should be treated with effective, evidence-based NVP interventions. Abstract: Background: Cross-sectional studies indicate an elevated prevalence of prenatal marijuana use in women with nausea and vomiting in pregnancy (NVP). However, it is unknown whether differences in marijuana use by NVP status have persisted over time as marijuana becomes more acceptable and accessible and prenatal use increases overall. We compared trends in prenatal marijuana use by NVP status in the first trimester of pregnancy using data from Kaiser Permanente Northern California's (KPNC) large healthcare system. Methods: The sample comprised KPNC pregnant women aged ≥12 who completed a self-administered questionnaire on marijuana use and a urine toxicology test for cannabis during standard prenatal care from 2009 to 2016. The annual prevalence of marijuana use via self-report or toxicology by NVP status was estimated using Poisson regression with a log link function, adjusting for sociodemographics and parity. We tested for linear trends and differences in trends by NVP. Results: Of 220, 510 pregnancies, 38, 831 (17.6%) had an NVP diagnosis. Prenatal marijuana use was elevated each year among women with NVP. The adjusted prevalence of use increased significantly from 2009 to 2016 at an annual rate of 1.086 (95%CI = 1.069–1.104) among women with NVP, from 6.5% (95%CI = 5.7%–7.2%) to 11.1% (95%CI = 0.2%–12.0%), and 1.069 (95%CI = 1.059–1.080) among women without NVP, from 3.4% (95%CI = 3.2%–3.7%) to 5.8% (95%CI = 5.5%–6.1%). Trends did not vary by NVP status. Discussion: The prevalence of prenatal marijuana use has remained elevated over time among women with NVP. Clinicians should ask pregnant patients about their reasons for marijuana use and treat NVP with evidence-based interventions.